Number of Fimbria of fallopian tubes - A postmortem study - Hena, Hasna; Qasim, Rubina; Ullah, MD Enayet; Ara, Shamim; Siddiqua, Dilruba; Jahora, Fatema (Update Dental College Journal, 2013)
Background: Fallopian tube is one of the vital organ for human fertility.This is where the sperm fertilizes the ovum and human life begins. Detailed morphological knowledge is essential for proper diagnosis and management of disease of fallopian tube. Study Design: Cross Sectional descriptive type of study. Place & period of study: Department of Anatomy, Dhaka Medical College, Dhaka from July 2008 to June 2009. Materials: 120 postmortem human fallopian tubes were collected from 60 unclaimed dead bodies that were under examination in the morgue of Department of Forensic Medicine, Dhaka Medical College, Dhaka. Methods: The samples were divided into three age groups: Group-A (10-13 years), Group-B (14-45 years) and Group-C (46-50 years). Results: The mean(±SD) number of fimbriae of the right & left Fallopian tubes were 21.20(±3.63) and 21.00(±4.00) in group A, 21.71(±2.13) and 21.53(±2.07) in group B and 20.90(±3.48) and 21.20± 2.30 in group C respectively.The highest mean number was found in group B and lowest mean number was in group A. The mean difference in number of fimbria of right and left Fallopian tube between Group-A, Group-B and Group-C were statistically not significant. Conclusion:In this study, the number of fimbriae does not vary in between right and left fallopian tubes, in any age group. DOI: http://dx.doi.org/10.3329/updcj.v2i1.13956 Update Dent. Coll. j: 2012; 2 (1): 21-24